Porcine epidemic diarrhea virus infection blocks cell cycle and induces apoptosis in pig intestinal epithelial cells. (October 2020) - Shen, Xuehuai; Yin, Lei; Pan, Xiaocheng; Zhao, Ruihong; Zhang, Danjun
Abstract: Porcine epidemic diarrhea virus (PEDV) is responsible for the acute infectious swine disease porcine epidemic diarrhea (PED). PED causes damage to the intestine, including villus atrophy and shedding, leading to serious economic losses to the pig industry worldwide. We carried out an in vitro study to investigate cell apoptosis and the cell cycle in a PEDV-infected host using transcriptomic shotgun sequencing (RNA-Seq) to study gene responses to PEDV infection. Results revealed that the PEDV infection reduced proliferation activity, blocked the cell cycle at S-phase and induced apoptosis in IPEC-J2 cells. The expression of gene levels related to ribosome proteins and oxidative phosphorylation were significantly up-regulated post-PEDV infection. Although the significantly down-regulated on PI3K/Akt signaling pathway post-PEDV infection, the regulator–related genes of mTOR signaling pathway exerted significantly up-regulated or down-regulated in IPEC-J2 cells. These results indicated that ribosome proteins and oxidative phosphorylation process were widely involved in the pathological changes and regulation of host cells caused by PEDV infection, and PI3K/AKT and mTOR signaling pathways played a vital role in antiviral regulation in IPEC-J2 cells. These data might provide new insights into the specific pathogenesis of PEDV infection and pave the way for the development of effective therapeutic strategies. Highlights: PEDV infection reduced proliferation activity, blocked cell cycle and induced apoptosis in IPEC-J2. PEDV infection significantly up-regulated the expression of ribosome proteins and oxidative phosphorylation process. PI3K/Akt and mTOR signaling pathways played a vital role in modulating the effects of PEDV infection.